1978
DOI: 10.1111/j.1600-0773.1978.tb02204.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Disulfiram‐Like Effect of Coprine, the Pharmacologically Active Principle of Coprinus atramentarius

Abstract: Coprine or disulfiram was given to rats in various doses at various time intervals before the administration of 2 g/kg ethanol. The ratio acetaldehyde/ethanol in the alveolar air was measured by gas chromatography and was taken as an index of the aldehyde dehydrogenase (ALDH) activity. The activity of dopamine β‐hydroxylase (DBH) was estimated in the same animals by measuring the amount of 14C‐octopamine formed from 14C‐tyramine in the heart. Coprine and disulfiram both caused an increase in the acetylaldehyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…[79]. C. atramentarius contains coprine, a pro-toxin of 1-amino-cyclopropanol which inhibits acetaldehyde dehydrogenase; however, it does not inhibit dopamine-beta hydroxylase, as does disulfiram [79,80]. A disulfiram-like reaction ensues if ethanol is ingested within 30 min to 3 days after mushroom ingestion and can occur within several minutes of ingesting ethanol [79].…”
Section: Gastritis/gastroenteritis Reactionsmentioning
confidence: 99%
“…[79]. C. atramentarius contains coprine, a pro-toxin of 1-amino-cyclopropanol which inhibits acetaldehyde dehydrogenase; however, it does not inhibit dopamine-beta hydroxylase, as does disulfiram [79,80]. A disulfiram-like reaction ensues if ethanol is ingested within 30 min to 3 days after mushroom ingestion and can occur within several minutes of ingesting ethanol [79].…”
Section: Gastritis/gastroenteritis Reactionsmentioning
confidence: 99%
“…The esterase activity of ALDH is also inhibited, albeit to a lesser extent compared with the dehydrogenase activity (Marchner and Tottmar, 1983). Unlike disulfiram (see below), it does not inhibit dopamine ␤-hydroxylase (Carlsson et al, 1978;Tottmar and Hellstrom, 1979). Despite its potency at inhibiting ALDH activity, mutagenic and gonadotoxic side effects prevented further pursuit of this compound as a candidate for drug development (Michelot, 1992).…”
Section: F Coprinementioning
confidence: 99%
“…Previous studies have shown that the inhibition of DBH and ALDH in disulfiram-treated rats is markedly different with respect to time-and doseresponse (Carlsson et al 1978;Deitrich & Erwin 1971). By using this difference, it was thought possible to gain some information about the relative importance of these two enzymes for the alcohol-sensitizing effects produced by disulfiram.…”
Section: Blood Pressure Response After Ethanol Administration To Disumentioning
confidence: 98%
“…The DBHactivity in the heart in vivo was estimated from the rate of formation of I4C-octopamine from injected ''C-tyramine (Almgren et a/. 1965;Carlsson et al 1978). I4C-tyramine (14 pg/kg, 4 pCi/kg) was injected intravenously to anaesthetized rats (hexobarbital sodium, 150 mg/kg, intraperitoneally).…”
Section: Determination Of Dopamine-p-hydroxylase (Dbh)-and Aldehyde-dmentioning
confidence: 99%